Analysis Policy Application a Corporate Social Responsibility (CSR) of PT. KITADIN on Embalut Village Community Sub-district of Tenggarong Seberang District of Kutai Kartanegara - Stevani Imelda (Jurnal Administrasi Bisnis Fisipol Unmul, 2021)
The company is here not only to achieve a goal, to get profit and to sustain a business but also to be responsible for the real growth af community welfare (stakeholders), espencially in communities around the company that have a direct or indirect impact on the company’s operational activities as outlined in the corporate sosial responsibility program. The implementation of the CSR program polic is stated more clearly in the Limited Liability Company Law (UUPT) Article 74 No. 40 of 2007. This study aims to identifity and describe the implementation of the corporate sosial responsibility polic of PT. KITADIN in the community if Embalut village can provide social, economic, and environmental benefits for the company. The research method used in this research is descriptive qualitative, with a research focus: the application of CSR policies in sosial development, economic development, environmental protection, and the suitability of planinning and implementing CSR The results of research in the implementation of the CSR policy of PT. KITADIN has provided benefits to society by providing several policies such as social development programs, economic development, and environmental improvement. This program has had a very good impact in increasing community independence and has had a good influence on the company, sunc as increasing reputation, trust, and building good relations between the company and the community. PT. KITADIN should do a follow-up on what is still needed by the people in Embalut village and more regularly review the programs that have been given. Meanwhile, in Embalut village, it is better if the program planning proposal is made approximately on month before the planning of the corporate social responsibility program starts and reports on the achievement of success in the CSR programs that have been given.